PENGARUH KECERDASAN INTELEKTUAL, KECERDASAN EMOSIONAL DAN KECERDASAN SPIRITUAL TERHADAP PEMAHAMAN AKUNTANSI - Suratman Suratman; Nanang Ari Utomo (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2021)
This study aims to determine the effect of intellectual intelligence, emotional intelligence, and spiritual intelligence on accounting understanding. The sampling method is purposive sampling and the sample used is 134 students from the Semarang University in 2018. The data collection technique is by distributing questionnaires. Analysis of the data in this study with linear regression with software smartPLS 3.2.9. The results of this study indicate that Intellectual Intelligence, Emotional Intelligence and Spiritual Intelligence have a simultaneous effect on Accounting Understanding. Partially, Intellectual Intelligence and Emotional Intelligence have no effect on Accounting Understanding, while Spiritual Intelligence has no effect on Accounting Understanding.